Urgency of Licensing Restriction in Joint Venture Companies Related to TKDN - Pratama, Toebagus Galang Windi (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2019)
Most companies that market their products in Indonesia in order to pass TKDN using the concept of Joint Venture agreements (PMA) often the parties working together are unbalanced in real terms the shares of foreign owners are greater than domestic shareholders. In such conditions the strong parties tend to impose their will on the weaker party. Therefore, according to the principle of freedom of contact in relation to the free market, in fully contracting is an affair of the parties, however legal protection and public interest are therefore required from government interference in the form of regulation or restrictions. The restrictions in regulating technology transfer from developed countries to developing countries aim to protect the interests of countries that divert technology because the inventor of the technology is considered to have made maximum efforts to find related technology but on the other hand the state is also obliged to protect and improve the welfare of its citizens from that, restrictions on patent licenses are needed so that the TKD is truly "real" and does not reduce the incoming FDI.Based on this, the authors formulated a number of issues namely: Why are restrictions on patent licenses needed and What are the legal consequences of limiting patent licenses . The results of the discussion show that the transfer of technology is needed for developing countries needed to advance their products in the era of globalization so that arrangements for it are needed so that in case of cooperation there is no inequality. And, the role of law in the policy of technology transfer to transform agrarian societies into industrialist societies. Here there is a dilemmatic situation on the one hand the acceleration of mastery of technology including the acceleration of development needs to be done by being open to the owners of capital and technology (which generally comes from developed countries), while on the other hand we still have to maintain national interests. Here is related to the authority of the state to regulate the process of technology transfer. In this global era, after the WTO agreement was reached, which was linked to 2 (two) technology transfer agendas, namely TRIMS and TRIPS. Foreign technology protection was very much needed in the context of foreign investment.